PERENCANAAN RUTE PENGIRIMAN UNTUK MEMINIMALKAN BIAYA TRANSPORTASI - Efzi, Rijani (Jurnal Teknik Industri, 2009)
PT. Indomarco Adi Prima represent one of the company which active in the distribution of product, handling of inefficient distribution represent main problem in this industry which cause the expense of high transportation. Of the condition needed some method to overcome the problem. Generalized Assignment method represents one of the methods which studying process delivery of goods to consumer in supply chain management is the routing and scheduling vehicles of deliveries. Especial target of this method is to plan the amount of proposal product allocation so that is later expected by minimization can the expense of product distribution. Before we apply Generalized Assignment method, is beforehand done by plotting and forecasting of request data 3 months come. Forecasting of demand by using method matching with result plotting of data, and then selected [by] smallest MAPE. After that result of the forecasting processed by using Generalized Assignment method. From data processing obtained by result with Generalized Assignment method (Pakis) obtained by cost-saving of distribution equal to Rp2.038.531,00/period of delivery or by cost-saving equal to 31.70%. While for (Klojen) obtained by cost-saving of distribution equal to Rp1.215.589,00/period of delivery or by cost-saving equal to 22.19%. The result for the distance after using Generalized Assignment method obtained (Pakis)by distance-saving of distribution equal to 116 km or by distance-saving equal to 18.86%. And result for the distance after using Generalized Assignment method obtained (Klojen) by distance-saving of distribution equal to 13 km or by distance-saving equal to 3.74%.